Nutritional Value with Quality of Late Season Cauliflower Varieties in Terai Region of Nepal - Giri, Hom Nath (International Journal of Applied Sciences and Biotechnology, 2020)
An experiment was carried out to assess the nutritional value along with quality of curds in late season cauliflower varieties at Rampur, Chitwan during November 2017 to March, 2018. The eleven late season cauliflower varieties were Freedom, Titan, Ravella, Amazing, Artica, Bishop, Casper, Indam 9803, NS 106, Snow Mystique and Snowball 16 which were introduced from USA, Europe, India and Nepal. The experiment was prepared in a Randomized Complete Block Design (RCBD) with four replications. The main objective of this study was to check the nutritional content, taste, compactness, appearance and freshness of the curds in eleven late season cauliflower varieties at Rampur, Chitwan. Nutritional value along with taste quality, compactness, appearance and freshness of the curds were measured after harvest. Maximum moisture and carbohydrate content was found in Freedom while higher crude fat was obtained in Titan and Bishop. Similarly, higher crude protein and crude fiber was found in NS 106. Significantly better taste score (8.8) was found in Snowball 16 than other varieties. Better compactness score of curd was found in Artica and Titan than other varieties. Significantly better appearance score (8.0) was found in Artica but poor appearance score was found in Casper than other varieties. At different intervals after harvesting of curds, significantly fresher curds were found in Artica than other varieties. In conclusion, NS 106 performed higher content of crude protein and crude fiber while Snowball 16 executed better tasty curds than other varieties. Artica also showed better performance on freshness of curds than other varieties. Int. J. Appl. Sci. Biotechnol. Vol 8(4): 427-431